Retrofits of a Partial Combustion Lance using a Computational Fluid Dynamics - Law, Woon Phui; Jolius, Gimbun (Universiti Teknikal Malaysia Melaka (UTeM), 2015)
This paper presents a computational fluid dynamics (CFD) simulation of a partial combustion lance (PCL) aiming to evaluate the effect of nozzle design and oxygen flowrate on its performance. At first, the modelling strategy was developed by evaluating the effect of discretization, pressure interpolation scheme and turbulence models on the prediction accuracy. Four turbulence models, namely standard k-ε (SKE), realizable k-ε (RKE), renormalized (RNG) k-ε and Reynolds stress model (RSM) were used. Combustion was modelled using the species transport model, whereas the heat transfer was calculated by considering a combined convection-radiation boundary condition. The best CFD prediction was obtained using the third-order MUSCL (Monotonic for upstream-centred scheme for conservation law), PRESTO (Pressure staggering option) pressure interpolation scheme and RSM, yielding an error of 2.23% from the experimentally measured temperature. The new nozzle design shows increases in excess of 70% of the peak combustion temperature of the PCL. It was found that 40% increase in oxygen flowrate increased the peak combustion temperature of the PCL by about 12%. Dual lance was found to be more effective than the single lance operating at a similar flowrate. The finding obtained from this work may be useful for design retrofits of a PCL.